Antioxidant Status of Serum Bilirubin, Uric Acid and Albumin in Pemphigus Vulgaris - Qurat-Ul-Ain, Wajieha Saeed, Farwa Nasir Khan, Aqsa Imtiaz, Nuzha Niazi, Mahym Mansoor, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine antioxidant status of serum bilirubin, uric acid and albumin in pemphigus vulgaris. Study Design: Cross sectional study Place of Study and Duration: This study was done at Department of Dermatology Mayo Hospital Lahore from July 11, 2019 to January 11, 2020. Methodology: All 60 cases meeting inclusion criteria was enrolled after taking informed consent, from outdoor Department of Dermatology Mayo Hospital Lahore. A total of 200 cases meeting inclusion criteria was taken after getting approval from CPSP. A brief demographic information and contact detail was taken. Venous blood was collected from each subject for the evaluation of Serum Bilirubin, Uric Acid and Albumin. Total bilirubin, direct bilirubin, indirect bilirubin, UA and albumin levels was determined using an automatic biochemical analyzer (Model 7600‐120; Hitachi High Technologies, Tokyo, Japan). All the values was recorded as per operational definition. Results: The mean age of patients was 40.08±12.89 years with minimum and maximum age as 18 and 60 years. There were 22(36.7%) male and 38(63.3%) female cases with higher female to male ratio. The mean BMI was 29.08±2.70 with minimum and maximum BMI as 24 and 33.90. The mean serum bilirubin level was 8.51±1.64µmol/L with minimum and maximum serum bilirubin was 5.80µmol/L and 11µmol/L. The mean uric acid levels in this study was 234.37±33.46µmol/L with minimum and maximum value as 160.00µmol/L and 280.00µmol/L. The mean Albumin level in this study was 34.20 ±3.69g/l with minimum and maximum albumin level as 29.00g/l and 41g/l. Conclusion: It is concluded that oxidative stress and antioxidant status are important in the pathogenic mechanism of PV. Hence by keeping these profile in mind that it can be of benefit to administer bilirubin, UA and albumin or their precursors as a replacement therapy to patients with PV who have low antioxidant status. Key Words: Antioxidant status, serum bilirubin, uric acid, albumin, pemphigus vulgaris.